Coaching & mentoring - MacLeod, Leo; Brounstein, Marty (--For dummies., 2023)
Coaching & Mentoring For Dummies is the playbook to help supervisors change their role from doer/manager to coach/mentor. Leadership and coaching expert Leo MacLeod shares the secrets of motivating employees to find purpose in their work and grow as independent problem solvers-without micromanaging them. Written for today's changing workplace, the book provides guidance on leading diverse teams, working with younger generations, and working remotely. This guide provides you with the skills to strengthen connections and pass on useful knowledge that will help teams elevate their productivity and quality of work. - Gain or improve the coaching skills that drive employee performance and commitment in diverse workforces - Encourage colleagues to deliver results and guide employees to think for themselves - Motivate teams, and navigate intergenerational issues - Be a sounding board for others and get the best out of your teams - Foster mentoring relationships that help employees grow and stay engaged. This is the perfect Dummies guide for anyone who wants to learn the best practices of coaching and mentorship in today's diverse, digital world.